2015
DOI: 10.1182/blood-2015-06-650242
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of hyperdiploidy in myeloma prognosis: which trisomies really matter?

Abstract: Key Points• In myeloma patients, trisomy 3 improved time to progression and trisomies 3 and/or 5 improved overall survival. • In contrast, trisomy 21 significantly worsened overall survival.The prognosis of multiple myeloma is mainly dependent upon chromosomal changes. The 2 major abnormalities driving poor outcome are del(17p) and t(4;14). However, the outcome of these high-risk patients is not absolutely uniform, with some patients presenting long survival. We hypothesized that these better outcomes might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 22 publications
6
63
0
2
Order By: Relevance
“…The presence of subclonal CA in patients with a HD karyotype is most likely because gains of odd-numbered chromosomes are highly associated with each other (supplemental Figure 3). 16 The events leading to trisomies in MM are not fully understood. Preclinical studies in Wilms tumor cells demonstrated that bipolar mitosis with missegregation of chromosomes during anaphase causes trisomies.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of subclonal CA in patients with a HD karyotype is most likely because gains of odd-numbered chromosomes are highly associated with each other (supplemental Figure 3). 16 The events leading to trisomies in MM are not fully understood. Preclinical studies in Wilms tumor cells demonstrated that bipolar mitosis with missegregation of chromosomes during anaphase causes trisomies.…”
Section: Discussionmentioning
confidence: 99%
“…The individual abnormalities t(4;14), 16,17 t(14;16), 17,18 and del(17p) 17,19 have been shown to be independent poor prognostic markers in MM. The findings from our analyses showed a consistent PFS benefit with IRd vs placebo-Rd across the different markers, with a HR of 0.596 (95% CI, 0.286-1.243) in patients with del(17p) and 0.645 (95% CI, 0.250-1.663) in patients with t(4;14).…”
Section: Org Frommentioning
confidence: 99%
“…[16][17][18][19] Additionally, gain of 1q21 on FISH has been shown to confer poor prognosis 17,20,21 ; in some reports, 1q21 amplification is considered a high-risk abnormality, 21,22 including in a 2016 consensus paper from the International Myeloma Working Group, 10 whereas other reports classify it as conferring intermediate or standard risk. 23,24 To date, although data on the use of novel agent-based treatments have demonstrated that these regimens improve outcomes in patients with MM vs previous or existing standards of care, progression-free survival The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients with UCA1 “high” expression levels were associated with presence of gain 1q21 or t(4;14), which have been previously described as unfavorable prognostic factors for MM . This observation was further supported via opposite, however not significant, association with UCA1 “low” expression group of patients and HY status standing as a favorable factor for MM prognosis . The “low/high” UCA1 groups of MM patients were further heterogeneous in biochemical parameters.…”
Section: Discussionmentioning
confidence: 52%